HUBUNGAN PENGETAHUAN IBU USIA PREMENOPAUSE TENTANG MENOPAUSE DENGAN KESIAPAN MENGHADAPI MASA MENOPAUSE DI PUSKESMAS SEI PANCUR KOTA BATAM TAHUN 2017 - Novianti, Rina; Yunita, Prasida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
The impact of high age of life expectation places most of aged women to complain about their premenopausal age. This issue happens as a signal that perhaps they are not ready, and the worse, many of them do not know about women menopausal phase on the other hand. Thus, this study aims to see the correlation of premenopausal age women knowledge about menopause with their readiness to face it. The research design of this study was an analytic survey with cross sectional approach. The population of this study is women aged 40 to 49 years old who attended Sei Pancur Health Centre through purposive sampling technique. The study was conducted on June 2017 by using questionnaires as the research instrument. Further, the data collection was analyzed by chi square statistical test. The result reveals 52.5% respondents have good knowledge level on menopause, nevertheless, 57.5% respondents admit that they do not ready yet for that. The Pearson correlation obtained from the test shows p-value of 0.01 < 0.05. Therefore, the researchers conclude that there is a significant correlation of premenopausal age women knowledge about menopause with their readiness to face the menopause phase particularly the ones came to Sei Pancur Health Centre of Batam City on June 2017. To suggest, it is hoped that the health center to be able to provide more detail information about the menopause both in and outside their working environment.